Utilizing Social Networks for User Model Priming: User Attitudes - DONOHOE, GARY JAMES; CONLAN, OWEN (My University, 2013)
Research on user modeling based on social network information has shown that some user characteristics can be accurately inferred from users? digital traces. This kind of information can be used to inform user models of adaptive systems for personalizing the system. This paper addresses a crucial question for practical application of this approach: Are users actually willing to provide their social Web profiles and how do they perceive this? An empirical study conducted with medical students shows that although participants are using social networks, they are reluctant about providing their identities and consider these portals rather private. The outcomes of the study uncover a clear need for further research on enhanced privacy and enhanced trust.
21st Conference on User Modeling, Adaptation, and Personalization
PUBLISHED
Keywords: user modeling; empirical study; social networks; privacy; user acceptance